School violence radiography (2020)
On this book it is described the conceptualizations about school violence, as well as the types of repertive school violenc. Besides that, it isanalyzed the educational public policies to prevent school violence and promote improvements in school coexistence in Latin-American. Furthermore is analyzed the research carried out which have been published about school violence, the topics with which is related and school mediation as a method of conflicto resolution and as a peace tool to promote a healthy school coexistence in diverse contexts